2002
DOI: 10.1017/s1323892200000570
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of the Case Manager in Workers' Compensation: Decision-Maker, System Player, Para Legal/Medical Specialist, Mediator or Enemy?

Abstract: This paper explores the complexities of the role of the workers' compensation case manager working for claims agents in South Australia. It provides a brief outline of the many skills required by case managers as they deal with the worker's injury, issues of compliance, the legislation, the social and psychological aspects of the worker's claim and the treatment and management of the worker's welfare. It describes the tensions brought about by the dual nature of the case manager's role that encompasses claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The researcher's familiarity with the area allowed effective management of the high volume of data in relation to the key issues. The distinct perspectives of different stakeholders can be seen in the resulting publications (see Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004. The comments quoted in the introductory material above also come from this source.…”
Section: Research Findings Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher's familiarity with the area allowed effective management of the high volume of data in relation to the key issues. The distinct perspectives of different stakeholders can be seen in the resulting publications (see Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004. The comments quoted in the introductory material above also come from this source.…”
Section: Research Findings Methodologymentioning
confidence: 99%
“…Clearly, it is important that all the stakeholders are given the opportunity to be equal contributors during the 'life' of a compensation claim. However, the degree of authority displayed by these two particular stakeholders (the GP and the case manager) frequently was reported as frustrating the management of resources, restricting input from others, impeding full restoration and, in some cases, increasing the longevity of the claim (see Roberts-Yates, 2002b;2004a).…”
Section: Problem Description: the Facts Of Social Power And Their Effmentioning
confidence: 99%
See 1 more Smart Citation
“…The case managers who were interviewed clearly expected the rehabilitation focus to be process-oriented because of the legislative requirements, although they admitted that these protocols allow for some movement and discretionary action on the part of the rehabilitation provider. Case managers preferred competent, focused, skilled providers who have a clear understanding of their role and are able to professionally manage the escalating emotions evident at various points along the process (see Roberts-Yates, 2002b). In fact, insurance companies have "preferred provider lists" from which the case manager selects rehabilitation counsellors to match the needs and personalities of specific workers:…”
Section: Case Managers' Perspectivesmentioning
confidence: 99%
“…They complained about poor communication channels where GPs left case managers out of the loop and medical specialists presented as professional strangers with limited involvement, frequently failing to complete medical reports in a clear and useful way. They reported that medical practitioners make too many assumptions about the worker's performance based on opinion and information provided by the worker (Roberts-Yates, 2002b). Their comments include the following:…”
Section: Case Managers' Perspectivesmentioning
confidence: 99%